Geologic mapping of the south polar feature of Vesta - Yingst, R. Aileen; Williams, David A.; Garry, W. Brent; Jaumann, Ralf; Pieters, Carle M.; Schenk, Paul M.; Buczkowski, Debra L.; Mest, Scott C.; Roatsch, Thomas; Russel, C.T. (2011)
Images of the asteroid and protoplanet 4Vesta by the Hubble Space Telescope in 1994 and 1996 revealed a ~460 km diameter feature at its south pole that was interpreted to be a large impact structure. We have utilized new images and data from the Dawn spacecraft to map the geology of this extensive feature approximately centered at the south pole of Vesta. Unit boundaries and feature characteristics were determined primarily using morphologic data; projected Framing Camera (FC) images were used as the base map. Color data was utilized to refine unit contacts and to separate compositional distinctions from differences arising from illumination or other factors. Those units that could be discerned both in morphology and in the color data were interpreted as geologically distinct units. The south polar feature consists of a semi-circular depression with a central hill that is characterized by smoother texture distinctive from the lower-lying surrounding terrain. A complex network of deep grooves and ridges is the primary characteristic of the feature floor; these grooves appear to trend along a north-south line projecting from the central hill. Color data suggests that the feature as a whole is more mafic than surrounding terrain. A steep semi-arcuate scarp bounds part of the outer perimeter of the south polar feature. The morphology data do not currently indicate the presence of a significant volume of impact melt (e.g., no regions or patches of smoother terrain are evident at the resolution available at this writing). Possible hypotheses for formation include impact and resulting faulting, fracturing and folding; endogenic activity such as upwelling or downwelling of a plume and subsequent structural disruption; or some combination of exogenic and endogenic processes. At the time of this abstract, the geologic map is consistent with any of these hypotheses. The authors gratefully acknowledge the support of the Dawn operational, instrument and science team.